The protective effects of Xuebijing injection on intestinal injuries of mice exposed to irradiation. Issue 6 (14th November 2022) - Dong, Yinping; Zhang, YuanYang; Wang, Xinyue; Li, Wenxuan; Zhang, Junling; Lu, Lu; Dong, Hui; Fan, Saijun; Meng, Aimin; Li, Deguan
Abstract: Background: Gastrointestinal (GI) injury is one of the most common side effects of radiotherapy. However, there is no ideal therapy method except for symptomatic treatment in the clinic. Xuebijing (XBJ) is a traditional Chinese medicine, used to treat sepsis by injection. In this study, the protective effects of XBJ on radiation‐induced intestinal injury (RIII) and its mechanism were explored. Methods: The effect of XBJ on survival of irradiated C57BL/6 mice was monitored. Histological changes including the number of crypts and the length of villi were evaluated by H&E. The expression of Lgr5 + intestinal stem cells (ISCs), Ki67 + cells, villin and lysozymes were examined by immunohistochemistry. The expression of cytokines in the intestinal crypt was detected by RT‐PCR. DNA damage and apoptosis rates in the small intestine were also evaluated by immunofluorescence. Results: In the present study, XBJ improved the survival rate of the mice after 8.0 and 9.0 Gy total body irradiation (TBI). XBJ attenuated structural damage of the small intestine, maintained regenerative ability and promoted proliferation and differentiation of crypt cells, decreased apoptosis rate and reduced DNA damage in the intestine. Elevation of IL‐6 and TNF‐α was limited, but IL‐1, TNF‐𝛽 and IL‐10 levels were increased in XBJ‐treated group after irradiation. The expression of Bax and p53 were decreased after XBJ treatment. Conclusions: Taken together, XBJ provides a protective effect on RIII by inhibiting inflammation and blocking p53‐related apoptosis pathway. Abstract : Xuebijing injections (XBJ) is a traditional Chinese medicine (TCM), approved for the sepsis treatment of by the China Food and Drug Administration. XBJ can effectively enhance the mice survival rate after total body irradiation (TBI). XBJ protects the crypt‐villus structure, maintains the proliferation and differentiation of the small intestine after TBI. XBJ reduces the expression of H2AX and the rate of apoptosis in the small intestine of irradiated mice. XBJ decreases the expression of p53 and inhibits the inflammation of the small intestine.